Health insurance politics in Japan : policy development, government, and the Japan Medical Association - Yamagishi, Takakazu, 1972- (Culture and politics of health care work., 2022)
"Covering the period from the Meiji Restoration to the Abe administration, this book examines what has driven the development of health politics, particularly regarding health insurance policy, of Japan and what role the government and medical professionals have played in the policy development"--